Monitoring and control of amygdala neurofeedback involves distributed information processing in the human brain. Issue 7 (30th March 2018) - Paret, Christian; Zähringer, Jenny; Ruf, Matthias; Gerchen, Martin Fungisai; Mall, Stephanie; Hendler, Talma; Schmahl, Christian; Ende, Gabriele
Abstract: Brain–computer interfaces provide conscious access to neural activity by means of brain‐derived feedback ("neurofeedback"). An individual's abilities to monitor and control feedback are two necessary processes for effective neurofeedback therapy, yet their underlying functional neuroanatomy is still being debated. In this study, healthy subjects received visual feedback from their amygdala response to negative pictures. Activation and functional connectivity were analyzed to disentangle the role of brain regions in different processes. Feedback monitoring was mapped to the thalamus, ventromedial prefrontal cortex (vmPFC), ventral striatum (VS), and rostral PFC. The VS responded to feedback corresponding to instructions while rPFC activity differentiated between conditions and predicted amygdala regulation. Control involved the lateral PFC, anterior cingulate, and insula. Monitoring and control activity overlapped in the VS and thalamus. Extending current neural models of neurofeedback, this study introduces monitoring and control of feedback as anatomically dissociated processes, and suggests their important role in voluntary neuromodulation.